Beach erosion and loss of protection environmental services in Cancun, Mexico. (15th April 2018) - Escudero-Castillo, Mireille; Felix-Delgado, Angélica; Silva, Rodolfo; Mariño-Tapia, Ismael; Mendoza, Edgar
Abstract: Human settlements in coastal zones have increased vulnerability to hydrometeorological phenomena in many places around the world. Of particular interest here is the case of Cancun, a luxurious tourist resort created in 1970 on the Caribbean coast of Mexico. The lack of regulations to control the expansion of tourist infrastructure on this barrier island, the disregard to environmental preservation, and the scarcity of external sediment sources have affected the natural balance of the beach-dune system over the intervening years. The consequences are chronic erosion of the beach and increased vulnerability to the extreme events of the last 30 years. Despite the implementation of some management strategies to halt erosion problems, the system still faces great risk. This paper shows the close relation that exists between the erosion of Cancun beach since the late 1960s and the spatial and temporal alteration of the ecosystem protection services triggered by the anthropogenic intervention on the barrier island. The analysis integrates the numerical modelling of the current state of the beach and the knowledge acquired from previous studies related to the wave field and circulation patterns under calm and extreme wave conditions. Cancun beach system showed to be still vulnerable to hydrometeorological threats. Highlights: Close relation between beach erosion and alteration of protection ecosystem service. High morphological variability and erosive tendency analysed since the 1970s. High susceptibility to erosion suggested by intense wave-driven currents. Cancun northern section identified as the most affected region by human action. Beach stability favoured by the 2010 nourishment for specific calm and storm wave conditions.